Comparing between Total Physical Response and Silent Way Method to Develop Students’ Speaking Ability - Andi Muhammad Syafri Idris; Abu Bakar Juddah; Nurhamdah Nurhamdah (LETS: Journal of Linguistics and English Teaching Studies, 2020)
The objective of the research is to get information about comparing between total physical response and silent way to develop speaking students’ ability at second grade senior high school 1 liliriaja Kab. Soppeng. This was a quasi-experimental research using two classes on pre-test and post-test design, the population of this research was second grade senior high school 1 liliriaja Kab. Soppeng. The technique to take the sample is cluster random sampling and the data was analyzed into descriptive statistics and T-test. The result of data analyzing shows that the students’ achievement of control class at pre-test 3,5625 and post test 5,59375, experimental class at pre-test 2,71875 and post-test 4,46875. While the result of t-test score was greater than t table. For the effectiveness of the speaking classroom context, the method tends to provide difficulties in practicing the speaking method. The researcher suggests the future researchers to conduct the relevant research by adding some new aspects into it. The aspects can be expanded in terms of the method used, number of research variables, research participants, etc